2019
DOI: 10.1080/13683500.2019.1668917
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect influence of experience quality on satisfaction: the importance of emotions

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…These were further explicated into four dimensions: hedonics, peace of mind, involvement, and recognition (Otto and Ritchie, 1996). Hedonics is defined as a set of emotional reactions associated with pleasure, enjoyment, the desire to experience various things, and sharing with others (Cervera-Taulet et al, 2019;González-Rodríguez et al, 2019;Schlesinger et al, 2020). Peace of mind refers to the need for relaxation, comfort, security, and privacy of body and mind (González-Rodríguez et al, 2019;Suhartanto et al, 2019;Schlesinger et al, 2020).…”
Section: Qsementioning
confidence: 99%
See 3 more Smart Citations
“…These were further explicated into four dimensions: hedonics, peace of mind, involvement, and recognition (Otto and Ritchie, 1996). Hedonics is defined as a set of emotional reactions associated with pleasure, enjoyment, the desire to experience various things, and sharing with others (Cervera-Taulet et al, 2019;González-Rodríguez et al, 2019;Schlesinger et al, 2020). Peace of mind refers to the need for relaxation, comfort, security, and privacy of body and mind (González-Rodríguez et al, 2019;Suhartanto et al, 2019;Schlesinger et al, 2020).…”
Section: Qsementioning
confidence: 99%
“…Hedonics is defined as a set of emotional reactions associated with pleasure, enjoyment, the desire to experience various things, and sharing with others (Cervera-Taulet et al, 2019;González-Rodríguez et al, 2019;Schlesinger et al, 2020). Peace of mind refers to the need for relaxation, comfort, security, and privacy of body and mind (González-Rodríguez et al, 2019;Suhartanto et al, 2019;Schlesinger et al, 2020). Involvement comprises the area of participation, education, decision-making, and control during the tour (Cervera-Taulet et al, 2019).…”
Section: Qsementioning
confidence: 99%
See 2 more Smart Citations
“…Graa et al (2014) also revealed that positive emotions felt by consumers were able to produce unplanned purchases. Consumers' positive emotions such as happiness and pleasure can encourage the creation of impulse buying behavior by consumers themselves (Chang et al, 2013;González-Rodríguez, Domínguez-Quintero, & Paddison, 2019).…”
Section: Effect Of Positive Emotions On Impulse Buying Behaviormentioning
confidence: 99%